2016
DOI: 10.3847/0004-637x/817/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Exploring X-Ray Binary Populations in Compact Group Galaxies With Chandra

Abstract: We obtain total galaxy X-ray luminosities, L X , originating from individually detected point sources in a sample of 47 galaxies in 15 compact groups of galaxies (CGs). For the great majority of our galaxies, we find that the detected point sources most likely are local to their associated galaxy, and are thus extragalactic X-ray binaries (XRBs) or nuclear active galactic nuclei (AGNs). For spiral and irregular galaxies, we find that, after accounting for AGNs and nuclear sources, most CG galaxies are either w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 93 publications
(148 reference statements)
1
8
0
Order By: Relevance
“…ultraluminous low-mass X-ray binaries (LMXBs; Angelini et al 2001;Colbert & Ptak 2002;Swartz et al 2004;Kim & Fabbiano 2004;Fabbiano et al 2006;Feng & Kaaret 2008. These demographic studies agree on two findings: a) Dwarf galaxies have been found to host more ULXs than expected given their SFR (Swartz et al 2008;Walton et al 2011;Plotkin et al 2014;Tzanavaris et al 2016). b) An observed excess of ULXs (and XRBs in general) in lowmetallicity galaxies (e.g., Mapelli et al 2010;Prestwich et al 2013;Brorby et al 2014;Douna et al 2015;Basu-Zych et al 2016) The excess in low-metallicty galaxies has highlighted the effect of metallicity on the accretor's mass and the evolutionary paths of ULXs (Heger et al 2003;Soria et al 2005;Belczynski et al 2010;Linden et al 2010;Mapelli et al 2011;Marchant et al 2017).…”
supporting
confidence: 61%
“…ultraluminous low-mass X-ray binaries (LMXBs; Angelini et al 2001;Colbert & Ptak 2002;Swartz et al 2004;Kim & Fabbiano 2004;Fabbiano et al 2006;Feng & Kaaret 2008. These demographic studies agree on two findings: a) Dwarf galaxies have been found to host more ULXs than expected given their SFR (Swartz et al 2008;Walton et al 2011;Plotkin et al 2014;Tzanavaris et al 2016). b) An observed excess of ULXs (and XRBs in general) in lowmetallicity galaxies (e.g., Mapelli et al 2010;Prestwich et al 2013;Brorby et al 2014;Douna et al 2015;Basu-Zych et al 2016) The excess in low-metallicty galaxies has highlighted the effect of metallicity on the accretor's mass and the evolutionary paths of ULXs (Heger et al 2003;Soria et al 2005;Belczynski et al 2010;Linden et al 2010;Mapelli et al 2011;Marchant et al 2017).…”
supporting
confidence: 61%
“…We compare our sample of groups with intergalactic light (IGL) to a sample of 15 compact groups (CG) [21]. The selection criteria of the CG sample are similar to the IGL sample, with requirements on size and redshift.…”
Section: Discussionmentioning
confidence: 99%
“…They have been removed from the CG sample for comparison. An outlier, a source in HCG 92 with luminosity 2.13 × 10 42 erg s −1 that has been identified with an AGN [21] and has not been plotted or included in the statistical comparison. The distribution of X-ray luminosities for the CG sample is shown in Figure 10 (left panel).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that both may have sizable effects on the XRB XLFs is consistent with the claimed redshift evolution of L X /M and L X /SFR, whereby the cosmic decline in mean stellar age and metallicity would be responsible for the inferred increase of both ratios with z (Lehmer et al 2016;Aird et al 2017, and references therein). However, a quantitative assessment of the role of age and metallicity in shaping the XRB XLFs functional form is inevitably challenging, as deep, high-statistics XLFs have only been assembled for nearby galaxies spanning a relatively limited range in both (see, e.g., Irwin et al 2004;Colbert et al 2004;Kaaret et al 2011;Prestwich et al 2013;Plotkin et al 2014;Basu-Zych et al 2016;Tzanavaris et al 2016;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%